OPTIMALISASI PENERIMAAN PASIEN BARU DALAM UPAYA PENINGKATAN MUTU RUANG RAWAT INAP RUMAH SAKIT. - Cahyaningrum, Ika; Tonga, Triputra Daud Umbu; Riada, Asriani Rosalia (Stikes Yarsi Mataram, 2025)
The quality of nursing care is one of the factors that influence the image of a hospital in the community. Nursing care begins as soon as a patient is admitted to the hospital. The admission of new patients involves receiving new patients and their families at the nursing care unit. The objective of this community service activity is to optimise the implementation of new patient orientation in the ward, with a programme that is carried out in accordance with the root causes of the existing problems. This activity was carried out by lecturers and students from the Nursing Professional Education Programme, Faculty of Health Sciences, Tribhuwana Tunggadewi University, Malang. The community service activity was conducted at Hospital X in Blitar, East Java. The steps in this community service activity are as follows: Identifying issues and needs of the partner through Focus Group Discussions (FGD), implementing and evaluating the programme according to the partner's needs. The outcomes of this community service activity include the development of a Standard Operating Procedure (SOP) for New Patient Admission, the implementation of SOP socialisation, and the implementation of the new patient admission process in accordance with procedures. Evaluation results showed an average increase of 36% in the implementation of the new patient admission process before and after SOP socialisation. Recommendations for the future include proposing the SOP to the hospital authorities and using media such as booklets or videos for new patient admission, as well as the need for continuous monitoring and evaluation to assess its effectiveness.